1 Hz Repetitive Transcranial Magnetic Stimulation of the Primary Motor Cortex: Impact on Excitability and Task Performance in Healthy Subjects - Engelhardt, Melina; Picht, Thomas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Neuronavigated repetitive transcranial stimulation (rTMS) at a frequency of 1 Hz was shown to reduce excitability in underlying brain areas while increasing excitability in the opposite hemisphere. In stroke patients, this principle is used to normalize activity between the lesioned and healthy hemispheres and to facilitate rehabilitation. However, standardization is lacking in applied protocols, and there is a poor understanding of the underlying physiologic mechanisms. Furthermore, the influence of hemispheric dominance on the intervention has not been studied before. A systematic evaluation of the effects in healthy subjects would deepen the understanding of these mechanisms and offer insights into ways to improve the intervention.Methods Twenty healthy subjects underwent five 15-minute sessions of neuronavigated rTMS or sham stimulation over their dominant or nondominant motor cortex. Dominance was assessed with the Edinburgh Handedness Inventory. Changes in both hemispheres were measured using behavioral parameters (finger tapping, grip force, and finger dexterity) and TMS measures (resting motor threshold, recruitment curve, motor area, and cortical silent period).Results All subjects tolerated the stimulation well. A pronounced improvement was noted in finger tapping scores over the nonstimulated hemisphere as well as a nonsignificant reduction of the cortical silent period in the stimulated hemisphere, indicating a differential effect of the rTMS on both hemispheres. Grip force remained at the baseline level in the rTMS group while decreasing in the sham group, suggesting the rTMS counterbalanced the effects of fatigue. Lastly, dominance did not influence any of the observed effects.Conclusions This study shows the capability of the applied low-frequency rTMS protocol to modify excitability of underlying brain areas as well as the contralateral hemisphere. It also highlights the need for a better understanding of underlying mechanisms and the identification of predictors for responsiveness to rTMS. However, results should be interpreted with caution because of the small sample size.
Keywords: repetitive transcranial magnetic stimulation; neuronavigated brain stimulation; motor cortex; cortical excitability